2014
DOI: 10.1039/c3sm52740a
|View full text |Cite
|
Sign up to set email alerts
|

Lipid oxidation induces structural changes in biomimetic membranes

Abstract: Oxidation can intimately influence and structurally compromise the levels of biological self-assembly embodied by intracellular and plasma membranes. Lipid peroxidation, a natural metabolic outcome of life with oxygen under light, is also a salient oxidation reaction in photomedicine treatments. However, the effect of peroxidation on the fate of lipid membranes remains elusive. Here we use a new photosensitizer that anchors and disperses in the membrane to achieve spatial control of the oxidizing species. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
127
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(173 citation statements)
references
References 33 publications
33
127
0
13
Order By: Relevance
“…The pure PlOOH membrane had the largest area per phospholipid and the lowest thickness among the investigated systems ( Figure 5). However, it was still stable, in qualitative agreement with earlier experimental results [46] and simulations [4]. Even when a larger membrane was simulated, no pore formation was observed ( Figure S6).…”
Section: Phospholipid Peroxidation In the Absence And Presence Of Chosupporting
confidence: 93%
See 1 more Smart Citation
“…The pure PlOOH membrane had the largest area per phospholipid and the lowest thickness among the investigated systems ( Figure 5). However, it was still stable, in qualitative agreement with earlier experimental results [46] and simulations [4]. Even when a larger membrane was simulated, no pore formation was observed ( Figure S6).…”
Section: Phospholipid Peroxidation In the Absence And Presence Of Chosupporting
confidence: 93%
“…These results are analogous to the -floating‖ of the OOH groups observed in phospholipid hydroperoxides [5, 38,46]. However, due to the rigidity of the sterol backbone, the whole molecule was forced to reorient.…”
Section: Effect Of Cholesterol Peroxidation On Sterol Backbone Orientsupporting
confidence: 79%
“…[7][8] While micropipette suction recently provided the first values for oxidized lipid area expansions, its implementation is not straightforward. In particular, pipettes have to be pulled and forged, coupled to a hydrostatic device before being monitored in the microscope objective vicinity through a high precision, i.e.…”
mentioning
confidence: 99%
“…In order to demonstrate that the changes on lipid bilayer architecture are induced by the 1 O 2 produced by JL103, instead of by the simple insertion of this compound in the membrane, we observed that the increase of POPC area is reverted by the addition of 15 mM sodium azide (NaN 3 ), a well know singlet oxygen trap, yielding values comparable to the previous controls. The increase on the POPC area after incubation with JL103 may be explained by the change on the projected area of POPC after addition of the hydroperoxide group, –OOH, to the double bond of the unsaturated lipid (Figure 4a), leading to a higher area-per-lipid due to the migration of the -OOH group to the polar plane of the bilayer 15, 16 .…”
Section: Resultsmentioning
confidence: 99%